(untitled) (Acta Scientiarum. Animal Sciences, 2018)
The objective of this study was to determine the genome association between markers of bovine LD BeadChip with dairy important traits. Information of breeding program of the Universidad Nacional de Colombia was used. BLUP-EBVs were used for dairy yield (DY), fat percentage (FP), protein percentage (PP) and somatic cell score (SCS). 150 animals were selected for blood or semen DNA extraction and genotyping with BovineLD BeadChip (Illumina). Autosomal information was retained and the editing information was performed using Plink v1.07 software. The effects of SNPs were determined by Bayes C with GS3 software. The minor allele frequency for most of the markers on the bead chip was high, which increases the probability of finding important loci segregating in the population. Estimations of fraction markers with an effect were close to zero in almost all cases. The most important markers were mapped by trait using ENSEMBL. A total of 6,510 autosomal SNPs were retained, out of which only a proportion with effect was taken from the mixed function of Bayes C. Important genes as ANKS1B, CLCN1, NMBR and CTSD, were found for each trait for AL, FP, PP and SCS respectively. Finally, Bayes C estimation allowed to identify specific SNPs possibly associated with QTLs.